The Road to Gaza - Shimshon Bichler; Jonathan Nitzan (Capital as Power - Toward a New Cosmology of Capitalism, 2024)
*** You can read, quote, reference and link this working paper, but you cannot reproduce or post it in any form unless permitted in writing by the authors ***** The war that started in 2023 between Hamas and Israel is driven by various long-lasting processes, but it also brings to the fore a new cause that hitherto seemed marginal: the armed militias of the Rabbinate and Islamic churches. The Rabbinate militias, embodied in Jewish settler organizations, have taken over not only Palestinian lands, but, gradually, also Israeli society. The Islamic militias, represented by Hamas and the Islamic Jihad, rose to prominence after the traditional resistance groups of the Palestinians – primarily the PLO and the PFLP and, by extension, also the Palestinian Authority – weakened and proved unable to reverse, let alone stop, the Israeli occupation. The rise of these militias, though, is hardly unique to Israel/Palestine, or even the Middle East. It is part of a broader, global process, in which `private' military organizations, financed by states, church-related NGOs and/or organized crime, fight for and against states as well as each other. The ascent of such groups is closely related to the decline of the nation-state and its popular armies, a model that developed in the wake of the French Revolution but no longer resonates with the increasingly globalized nature of capital accumulation. Our previous studies of Middle East wars emphasized the `state of capital' – our notion that the capitalist mode of power fuses state and capital into a single logic in which dominant capital groups are driven by the power quest for differential accumulation. We showed that, in the Middle East, this logic was imposed by a Weapondollar-Petrodollar Coalition of large oil and armament corporations, OPEC, financial institutions and construction firms, whose differential incomes and profits were tightly correlated with – and helped predict – the cyclical eruption of `energy conflicts'. But this mode of power comprises not two elements, but three. In addition to state and capital, it also includes the supreme-God churches, and in this paper we outline the role of these churches and their militias in capitalism generally and in Middle East wars specifically.
Keywords: P00; P18; P5; E31; H56; N4; 330; capitalism; capitalist mode of power; Christianity; church; dominant capital; energy conflicts; Gaza; Islam; Israel; Jehovah; Jesus; Judaism; Middle East; militias; modes of power; Occupied Territories; oligarchy; oil; Palestine; Rabbinate church; religion; state of capital; Weapondollar-Petrodollar Coalition